Penetasan telur penyu sisik (Eretmochelys imbricata) dengan kedalaman yang berbeda - Erlangga, Erlangga; Lestari, Ayu; Zulfikar, Zulfikar; Khalil, Munawar; Ezraneti, Riri (Acta Aquatica: Aquatic Sciences Journal, 2021)
This research was conducted from November 2018 until January 2019 which was held at the UPTD Conservation and Supervision of Marine Resources and Fisheries in West Sumatera, Pariaman City.  The aim of the research is to know hatchling hawksbill sea turtle eggs based on nest depth. The method used in this study is a nonfactorial randomized block design (RBD) consisting of 3 treatments and 3 replications. The treatments used were treatment A (with a depth of 30 cm incubation nest), treatment B (with a depth of incubation nest 40 cm), and Treatment C (with a depth of incubation nest 50 cm). The results of this study showed that hatching hawksbill eggs hatched very significantly, the best hatching percentage was in treatment A (30cm) with 78% hatching at 6:00 a.m. with hatching temperature range of 24-28oC, hatching pH of 6,6-6,8 and medium sized incubation sand with a size of 0.150 mm with a weight reaching 461 grams.Keywords: Hatching percentage, Hawksbill turtle, pH, Temperature